Exercise-Induced Brain Excitability Changes in Progressive Multiple Sclerosis: A Pilot Study. Issue 2 (April 2020) - Chaves, Arthur R.; Devasahayam, Augustine J.; Kelly, Liam P.; Pretty, Ryan W.; Ploughman, Michelle
Abstract : Background and Purpose: Even a single bout of aerobic exercise (AE) enhances corticospinal excitability (CSE), a biomarker of neuroplasticity. Because neurodegeneration limits capacity for neuroplasticity, it is not clear whether AE would induce CSE changes in people with progressive multiple sclerosis (MS). Methods: People with progressive MS (n = 10) requiring ambulatory assistive devices completed a graded maximal exercise test. Dual-energy x-ray absorptiometry was used to quantify body fat and lean mass. Before and following one 40-minute AE session using body weight–supported (<10% support) treadmill at moderate intensity, CSE was measured using transcranial magnetic stimulation. Variables included resting and active motor thresholds, motor evoked potential (MEP) amplitudes, recruitment curves, and length of the cortical silent period (CSP). Results: Aerobic exercise reduced inhibition (shorter CSP) and increased excitation (increased MEP amplitude) only in the hemisphere corresponding to the stronger hand. Controlling for age, higher fitness and lower body fat significantly predicted exercise-induced reduction in resting motor threshold (Δ R 2 = +0.458, P = 0.046) and CSP (Δ R 2 = +0.568, P = 0.030), respectively. Discussion and Conclusions: Despite high levels of disability, capacity for exercise-induced neuroplasticity was retained among people with progressive MS. The hemisphere contralateral to the weaker hand was resistant to exercise-induced CSE changes, suggesting less neuroplastic potential. Lower fitness and higher body fat were associated with diminished exercise-induced CSE benefits, suggesting that therapists should consider interventions aimed at improving fitness and combating sedentarism to ultimately enhance the benefits of exercise on the brain. Video Abstract available for more insights from the authors (see the Video, Supplemental Digital Content 1, available at: http://links.lww.com/JNPT/A302 ). Abstract : Supplemental Digital Content is Available in the Text.